GeTe Nanosheets as Theranostic Agents for Multimodal Imaging and Therapy of Inflammatory Bowel Disease. (7th October 2021) - Song, Jun Ho; Yoon, Taejun; Lee, Sun‐Mi; Mun, Chin Hee; Kim, Dasol; Han, Jieun; Kim, Ju‐Won; Bae, Yonghee; Kim, Taehee; Park, Young Nyun; Cho, Mann‐Ho; Park, Yong‐Beom; et al.
Abstract: Recently, 2D nanomaterials have received considerable attention in nanomedicine due to their intrinsic optical properties, biocompatibility, and therapeutic effect. Here, 2D germanium telluride (GeTe) nanosheets coated with polyvinylpyrrolidone (PVP) (GeTe‐PVP NSs) developed as theranostic agents are reported that can be used for multispectral optoacoustic tomography (MSOT) and fluorescence imaging and therapy of inflammatory bowel disease (IBD). GeTe‐PVP NSs, fabricated by simple sonication in ethanol and PVP, show broad optical absorption in visible and near‐infrared (NIR) ranges (400–1200 nm) and have intrinsic fluorescence properties. Thus, they provide deeper ex vivo and in vivo MSOT tissue images than gold nanorods or indocyanine green with strong optical absorption in the first NIR window (700–900 nm). In addition, when orally administered to IBD mice, GeTe‐PVP NSs exhibit therapeutic efficacy similar to or higher than sulfasalazine, with strong accumulation at inflammatory colon sites. This demonstrates that oral administration of GeTe‐PVP NSs may be used to treat inflammatory diseases in the gastrointestinal tract. Abstract : Germanium telluride–polyvinylpyrrolidone nanosheets (GeTe–PVP NSs) prepared using a simple top‐down method show broad absorption and fluorescence spectra, enabling them to act as multimodal contrast agents for multispectral optoacoustic tomography and fluorescence imaging. In addition, GeTe–PVP NSs exhibit therapeutic effects in mitigating inflammatory colitis, suggesting that the oral administration of GeTe–PVP NSs may be used to treat inflammatory bowel diseases.